Material for a history of Pope Alexander VI, his relatives, and his time - De Roo, Peter (Universal knowledge Foundation, 1924)
v. I--Family de Borgia; v. II--From the cradle to the throne; v. III--Pope Alexander VI as a supreme pontiff; v. IV--Pope Alexander VI as a temporal prince; v. V--Alexander VI and the Turks. His death and character.